1999
DOI: 10.1016/s0041-1345(99)00256-0
|View full text |Cite
|
Sign up to set email alerts
|

Increased bile duct complications and/or chronic rejection in crossmatch positive human liver allografts

Abstract: Bile duct complications continue to be a significant cause of bile morbidity after orthotopic liver transplantation, with an incidence of 7% to 34% of patients. 1,2 Bile of duct obstruction, usually due to strictures, biliary leakage, and/or cholangitis, accounts for the majority of these complications. In contrast, although low incidence of chronic rejection has been reported under FK 506-based immunosuppression in early trials of liver transplantation, 3 chronic rejection after liver transplantation occurs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
18
2

Year Published

2005
2005
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 17 publications
2
18
2
Order By: Relevance
“…The first potential correlation between a positive T cell cross-match and graft injury was reported in 1999. 14 In this retrospective analysis, the incidence of biliary complications during the average follow-up of 7 years was found to be 36.8% for cross-match-positive recipients and 10.2% for cross-match-negative recipients. According to a more recent analysis of a single-center experience, 21 circulating DSAs were documented in 7 of 10 liver transplant recipients with biopsy-proven ductopenia.…”
Section: Human Leukocyte Antigen Antibodies and Graft Injury/ Survivalmentioning
confidence: 73%
“…The first potential correlation between a positive T cell cross-match and graft injury was reported in 1999. 14 In this retrospective analysis, the incidence of biliary complications during the average follow-up of 7 years was found to be 36.8% for cross-match-positive recipients and 10.2% for cross-match-negative recipients. According to a more recent analysis of a single-center experience, 21 circulating DSAs were documented in 7 of 10 liver transplant recipients with biopsy-proven ductopenia.…”
Section: Human Leukocyte Antigen Antibodies and Graft Injury/ Survivalmentioning
confidence: 73%
“…7b) [94] and independent of ACR [87] where it mimics biliary obstruction with portal oedema and a ductular reaction [87]. C4d staining has been demonstrated in CR [30], a high incidence of anti-tissue antibodies has been found in patients experiencing CR [32,69] and there is an increased incidence of CR in patients with preformed DSAs [99], all of which suggest that AMR plays a role in the development of CR.…”
Section: Antibody-mediated Rejectionmentioning
confidence: 99%
“…With respect to graft complications, the Mayo group in 1988 observed a greater frequency of vanishing bile duct syndrome in positive crossmatch recipients 13. Approximately a decade ago, the Pittsburgh group reported an increased incidence of biliary complications and chronic rejection in recipients with a positive T cell crossmatch 14. Finally, in a recent report by Opelz et al,15 a positive T cell crossmatch in primary LT recipients was found to be significantly associated with impaired graft survival.…”
mentioning
confidence: 99%